Finite Element Analysis of Drawing Wire in Cassette Roller Die (Part 2). (2016) - Mihu, Adriana-Maria; Sas-Boca, Ioana Monica; Marian, Ionut; Mihu, Iulian Sebastian; Ianc, Dorina Simona; Nistor, Liviu; Ilutiu-Varvara, Dana-Adriana
Abstract: A complex study of the drawing process with cassette roller die, of the round wires is presented through 3D finite element simulations. The geometrical model is used for the wire and also for the device. The results of the numerical simulations are being compared with the theoretical analysis previously performed. This paper presents and analyses the influence of the variation process parameters such as: friction coefficient, radius of the working rollers, also initial and final diameter of the billet in the drawing process with cassette roller die. The comparison between drawing forces according to the stroke of wire drawing-in implement to different parameters values, concord in a numerical model predictions, thus validating the theoretical analysis.